Achieving sustainability using creativity, innovation, and education a multidisciplinary approach - Fields, Ziska, 1970- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"This publication will not only facilitate in identifying the important creativity, innovation and education mechanisms, frameworks, competencies, and skills, which is imperative for a sustainable planet and economic development but will also increase the development, knowledge and understanding of creativity, innovation and education needed now and in the future"--